Effect of rumen degradable protein and sulfur supplementation on in vitro digestibility and ruminal fermentation. Issue 1 (January 2022) - Rosmalia, A; Astriani; Sahroni, W P; Permana, I G; Despal
Abstract: The availability of nitrogen and sulfur in the rumen should be synchronized to generate microbial protein synthesis. This study aimed to evaluate rumen degradable protein and sulfur supplementation on in vitro digestibility and ruminal fermentation. The experimental design was a 4 x 3 factorial randomized block design. Factor 1 was RDP levels (%CP) (R1= 60%; R2= 55%; R3= 50%; R4= 45%), and factor 2 was sulfur supplementation (S1= 0%; S2= 0.1%; S3= 0.2%). Data were analyzed with ANOVA followed by the Duncan test. The result showed that sulfur supplementation improved DMD and OMD without changes in rumen pH. NH3 concentration was influenced by RDP levels. Treatment R1 had the highest NH3 concentration (7.03 mM). There was an interaction of two factors on total VFA concentration. The combination of R1 and S2 resulted in the highest total VFA concentration than others. The total bacteria population increased with increasing RDP levels. Protozoa population was affected by RDP levels and sulfur supplementation. This study concluded that a combination of 60% RDP and 0.2% sulfur supplementation resulted in the best ration to improve ruminal fermentation and digestibility.